Tape strips from early‐onset pediatric atopic dermatitis highlight disease abnormalities in nonlesional skin. Issue 1 (20th August 2020) - Pavel, Ana B.; Renert‐Yuval, Yael; Wu, Jianni; Del Duca, Ester; Diaz, Aisleen; Lefferdink, Rachel; Fang, Milie M.; Canter, Talia; Rangel, Stephanie M.; Zhang, Ning; Krueger, James G.; Paller, Amy S.; et al.
Abstract: Background: Skin biopsies promote our understanding of atopic dermatitis/AD pathomechanisms in infants/toddlers with early‐onset AD, but are not feasible in pediatric populations. Tape strips are an emerging, minimally invasive alternative, but global transcriptomic profiling in early pediatric AD is lacking. We aimed to provide global lesional and nonlesional skin profiles of infants/toddlers with recent‐onset, moderate‐to‐severe AD using tape strips. Methods: Sixteen tape strips were collected for RNA‐seq profiling from 19 infants/toddlers (<5 years old; lesional and nonlesional) with early‐onset moderate‐to‐severe AD (≤6 months) and 17 healthy controls. Results: We identified 1829 differentially expressed genes/DEGs in lesional AD and 662 DEGs in nonlesional AD, vs healthy skin (fold‐change ≥2, FDR <0.05), with 100% sample recovery. Both lesional and nonlesional skin showed significant dysregulations of Th2 (CCL17 and IL4R) and Th22/Th17 (IL36G, CCL20, and S100As)‐related genes, largely lacking significant Th1‐skewing. Significant down‐regulation of terminal differentiation (FLG and FLG2), lipid synthesis/metabolism (ELOVL3 and FA2H), and tight junction (CLDN8) genes were primarily seen in lesional AD. Significant negative correlations were identified between Th2 measures and epidermal barrier gene‐subsets and individual genes (FLG with IL‐4R and CCL17; r < −0.4, P < .05). Significant correlations were also identified between clinical measures (body surface area/BSA, pruritus ADQ, and transepidermal water loss/TEWL) with immune and barrier mRNAs in lesional and/or nonlesional AD (FLG/FLG2 with TEWL; r < −0.4, P < .05). Conclusion: RNA‐seq profiling using tape strips in early‐onset pediatric AD captures immune and barrier alterations in both lesional and nonlesional skin. Tape strips provide insight into disease pathomechanisms and cutaneous disease activity. Abstract : Tape strips are collected for RNA‐seq profiling from 19 infants/toddlers (ages 0‐5 years; lesional and nonlesional) with early‐onset (≤6 months), moderate‐to‐severe AD and 17 healthy controls. We identify 2491 differentially expressed genes in AD vs healthy skin. We observe significant dysregulation of Th2 and Th22/Th17‐related markers, largely lacking Th1 skewing. Significant decreases in barrier‐related genes are seen primarily in lesional skin. Abbreviations: AD, atopic dermatitis; DEGs, differentially expressed genes.